Ergasilus chelangulatus sp. nov. (Copepoda: Ergasilidae) a branchial parasite of the freshwater catfish, Pimelodus maculatus from the upper São Francisco River, Brazil - Thatcher,Vernon E. (2008)
Ergasilus chelangulatus sp. nov. is described from the freshwater fish, Pimelodus maculatus Lacépède, 1803 (Siluriformes: Pimelodidae) of the upper São Francisco River, Minas Gerais State, Brazil. The new species is based on female specimens and the male is unknown. This species has a serrate seta on exopod one and a two-segmented first endopod, as do most Amazonian species of this genus. The body is elongate and produced anteriorly. The antennae are elongate and have prominent sensilla on segments two and three. Ergasilus chelangulatus sp. nov. can be distinguished from all known species of Ergasilus by the fourth antennal segment (claw) which is bent at nearly a right angle.